2013
DOI: 10.1103/physrevlett.111.030602
|View full text |Cite
|
Sign up to set email alerts
|

Maxwell’s Refrigerator: An Exactly Solvable Model

Abstract: We describe a simple and solvable model of a device that -like the "neat-fingered being" in Maxwell's famous thought experiment -transfers energy from a cold system to a hot system by rectifying thermal fluctuations. In order to accomplish this task, our device requires a memory register to which it can write information: the increase in the Shannon entropy of the memory compensates the decrease in the thermodynamic entropy arising from the flow of heat against a thermal gradient. We construct the nonequilibri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
222
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(226 citation statements)
references
References 47 publications
2
222
1
1
Order By: Relevance
“…It was shown that, for a system with finite memory, the cost of bits erasure nullifies any gain from such a demon [2][3][4][5][6][7]. However, it was not until recently that Sagawa and Ueda reached a general upper bound on the amount of work that can be extracted [8,9], which was also demonstrated experimentally [10,11].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was shown that, for a system with finite memory, the cost of bits erasure nullifies any gain from such a demon [2][3][4][5][6][7]. However, it was not until recently that Sagawa and Ueda reached a general upper bound on the amount of work that can be extracted [8,9], which was also demonstrated experimentally [10,11].…”
Section: Introductionmentioning
confidence: 93%
“…The equations defining both problems, (2) and (10), are the same if one renames b X|Y as v f and o X as 1/P X . The analogy also holds for the optimal strategy in both problems, presented in (4) and (11), and the maximum gain, presented in (6) and (12), where log S n is renamed W n /k B T . Analogous to the way bits of side information are converted into wealth in gambling, bits of measurements are converted into work in the Szilard Engine.…”
Section: Analogymentioning
confidence: 99%
“…We believe that similar extensions can be offered also for the other variations of this model, that appear in [1], [2], [3], and [15], as mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…It may also act as an eraser, which implements the opposite process of losing energy while erasing information, that is, decreasing the entropy. Several variations on this model, based on similar ideas, were offered in some subsequent works, e.g., [1], [2], [3], and [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation